Win every argument : the art of debating, persuading, and public speaking - Hasan, Mehdi, 1979- (Henry Holt and Company, 2023)
"MSNBC's Mehdi Hasan isn't one to avoid arguments. He relishes them, as the lifeblood of democracy and the only surefire way to establish the truth. Arguments help us solve problems, uncover new ideas we might not have considered, and nudge our disagreements toward mutual understanding. A good argument, made in good faith, has intrinsic value-and can also simply be fun. Arguments are everywhere-and especially given the fierce debates we're all embroiled in today, everyone wants to win. In this riveting guide to the art of argument and rhetoric, Hasan shows you how. As a journalist, anchor, and interviewer who has clashed with politicians, generals, spy chiefs, and celebrities from across the world, Hasan reveals his tricks of the trade for the first time. Win Every Argument shows how anyone can communicate with confidence, rise above the tit for tats on social media, and triumph in a successful and productive debate in the real world. Whether you are making a presentation at work or debating current political issues with a friend, Mehdi Hasan will teach you how to sharpen your speaking skills to make the winning case"--